The Concept of the Heart in Spanish Prose: Cognitive and Cultural Perspectives - Djalilova Sarvaroy Mexrojovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract: This article explores the conceptualization of the heart in Spanish prose, focusing on the interaction between cognitive metaphor, emotional representation, and cultural symbolism. Drawing on conceptual metaphor theory and narrative studies, the research examines how the heart functions as a central symbol in Spanish literary texts from the 19th to the 21st century. The study identifies recurring metaphorical patterns in which the heart is associated with emotion, morality, identity, and relationality. The analysis reveals that Spanish prose writers frequently employ heart imagery to construct psychological depth, mediate interpersonal relations, and express moral or ethical dimensions of characters. Furthermore, the symbolic heart serves as a cultural marker, reflecting social values, gender norms, and historical perceptions of affectivity. The findings contribute to a better understanding of the interplay between cognitive metaphor, literary style, and cultural models in Spanish narrative discourse.